5 - Poltergeist II drawings 1983-1985 - Frey, Patrick 1949-; Koller, Andreas 1983- (Edition Patrick Frey, 2021)
The facsimile edition of the visionary sketches and notes of the surrealist master for Brian Gibson's horror film Poltergeist II, as well as drafts of letters to Gibson
Keywords: Giger, H. R. -- 1940-2014; Geschichte 1983-1985; Zeichnung; Gibson, Brian / Poltergeist II; Bildband